Gender Issues in Sexual Fulfillment; Nigerian Situation - Akanle, F.F; Ola, Tolulope Monisola (Mediterranean Journal of Social Sciences, 2012)
For many married women sexual relationship is hardly enjoyable, is it is more of a conjugal function than anenjoyable activity and many are in a violent relationship. This study therefore investigate the feelings of women concerning theirsexuality, what percentage of women have pleasurable and fulfilled sexual life and those things which women count as sexualfulfillment. A descriptive research design was used. The population consists of women aged 18-60 years and who are eitherliterate or non-literate. A total of number 200 women were selected using simple random sampling technique, a self-constructedquestionnaire was used to collect the data which was analyzed using percentages, cross tabulation and T-test. The findingsshow even when women have sex regularly most respondent do not have satisfactory sexual life.